Investigation of the functionality of electronic data capture and management systems for use in a modern animal health industry - Laporte, Ashlea Ellen (Kansas State University, 2024)
Electronic data capture (EDC) systems work to supplement or replace traditional paper record documentation in many industries. Within both human and animal healthcare industries clinical trial studies serve to benefit from EDC for efficiency and cost perspectives. This allows for a faster timeline to new medicinal products being available to markets in both fields. The animal health industry has not adopted implementation of EDC as readily as some industries and lags behind human health industries which may be explained by an easier path to implementation based on infrastructure that is already in place within hospitals and doctors’ offices. Animal producer industries, and the software available to those facets of the market, may be adapted or used to drive the use of EDC in clinical trials or other registration related animal studies. With focus on cattle producers a landscape analysis was performed to identify ranch management software available to the cow-calf industry. Using a search engine and application store search 23 EDC software programs were identified, analyzed, and further categorized based on their capabilities for technology integration, analytic options, and inventory features. Software capable of documenting relevant veterinary care aspects has the highest potential for crossover uses within the animal health industry. With the growth of infrastructure available to the animal health industry the implementation will only be delayed by the extrinsic nature of contract or external laboratory studies being commonplace. The benefits to EDC alone have not been enough to drive the animal health industry into full implementation. With further advancements within the human health industry, new software program availability for animal producers, and acquisition of software companies by animal health driven companies, this may eventually lead to improved implementation in the modern animal health industry in the future.
Keywords: Electronic data capture; Animal health industry; Data management systems